2019
DOI: 10.1002/ijc.32306
|View full text |Cite
|
Sign up to set email alerts
|

Fibulin‐7 is overexpressed in glioblastomas and modulates glioblastoma neovascularization through interaction with angiopoietin‐1

Abstract: Glioblastoma (GBM) is pathologically characterized by highly malignant neoplastic cells, focal necrosis and aberrant blood vessels composed of disorganized endothelial cells and pericytes. The recent cancer microarray database revealed upregulation of fibulin‐7 (Fbln7), a member of the fibulin family, but provided no information on the tissue localization or biological function. In the present study, we demonstrated that Fbln7 is markedly overexpressed by the GBM tissue among astrocytic tumors, and immunolocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Among the top upregulated genes in the TdT OSX single positive cells versus the double negative ( Table 1 ) we found several markers expressed by osteolinage cells, such as fibromodulin ( Fmod ), a binding protein regulating bone mineralization ( Gori et al, 2001 ) and also involved in TGF β signaling during cancer pathogenesis ( Pourhanifeh et al, 2019 ), Collagen 24a1 ( Col24a1 ), known to modulate collagen chain trimerization ( Koch et al, 2003 ; Matsuo et al, 2006 ), Frem1 , a protein involved in the formation and organization of basement membranes ( Vissers et al, 2011 ), and Msx1 , a transcription factor important in craniofacial bone development ( Orestes-Cardoso et al, 2002 ). TdT OSX single positive cells also expressed high levels of fibulin 7 ( Fbln7 ), a cell adhesion molecule overexpressed in glioblastoma by pericytes and involved in neovascularization ( de Vega et al, 2019 ; Ikeuchi et al, 2018 ). Such result confirmed the osteolineage nature of the TdT OSX + cells and indicated their tumor supporting role.…”
Section: Resultsmentioning
confidence: 99%
“…Among the top upregulated genes in the TdT OSX single positive cells versus the double negative ( Table 1 ) we found several markers expressed by osteolinage cells, such as fibromodulin ( Fmod ), a binding protein regulating bone mineralization ( Gori et al, 2001 ) and also involved in TGF β signaling during cancer pathogenesis ( Pourhanifeh et al, 2019 ), Collagen 24a1 ( Col24a1 ), known to modulate collagen chain trimerization ( Koch et al, 2003 ; Matsuo et al, 2006 ), Frem1 , a protein involved in the formation and organization of basement membranes ( Vissers et al, 2011 ), and Msx1 , a transcription factor important in craniofacial bone development ( Orestes-Cardoso et al, 2002 ). TdT OSX single positive cells also expressed high levels of fibulin 7 ( Fbln7 ), a cell adhesion molecule overexpressed in glioblastoma by pericytes and involved in neovascularization ( de Vega et al, 2019 ; Ikeuchi et al, 2018 ). Such result confirmed the osteolineage nature of the TdT OSX + cells and indicated their tumor supporting role.…”
Section: Resultsmentioning
confidence: 99%
“…However, it remains unclear regarding the association between the other genes and TNBC physiology, which require further study. Fibulin 7 has been previously reported to participate in the regulation of aberrant neovascularization by modulating the angiopoietin-1/angiopoietin-2-Tie2 axis (64). A previous study has shown that the cartilage intermediate layer protein gene is differentially expressed in differentiated thyroid carcinomas in comparison with normal thyroid tissues (65).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, those contained in α-granules play a pivotal role during platelet-cancer crosstalk (Table 2). Endostatin, TSP-1, angiostatin ↓ angiogenesis [107,108] Ang-1: angiopoietin-1; EGF: endothelial growth factor; MK: megakaryocytes; NK: natural kill cells; PAI-1: plasminogen activator inhibitor-1; PDGF-BB: Platelet-derived growth factor BB; TF: tumor necrosis factor; TSP-1: thrombospondin-1; VEGF Vascular endothelial growth factor.…”
Section: Platelet-derived Bioactive Compoundsmentioning
confidence: 99%
“…In proteomic studies, α-granules also have been shown to contain a plethora of angiogenesis inhibitors, including endostatin, platelet factor-4, thrombospondin-1, α 2 -macroglobulin, plasminogen activator inhibitor-1 and angiostatin. Therefore, activated platelets can organize regulatory proteins in the α-granules in order to selectively address the release of pro-or anti-angiogenic factors, depending on which different sets of α-granules are segregated [107,108]. Although cancer cells might have the ability to provoke preferential release of pro-angiogenic mediators from platelet α-granules, in order to create a dynamic microenvironment favorable for their growth and survival [107], several experimental and clinical data point out that platelet secretion in the tumorigenic microenvironment might also be oriented towards an anti-angiogenic effect.…”
Section: Platelet-derived Bioactive Compoundsmentioning
confidence: 99%
See 1 more Smart Citation